Status of the homeostasis in patients with puberty uterine bleeding - L. S. Sotnikova; R. F. Nasyrova; A. M. Dygai; V. V. Novitsky; Ye. V. Beloborodova; T. F. Agranovich (Бюллетень сибирской медицины)
In this article the analisis of homeostatic status in 590 patients with puberty uterine bleeding has being presented. We found the following systemic changes in studies of erythron, hormonal status, immunity and tonus vegetative nervous system.